Impact of stocking density on growth and production performance of monosex tilapia (Oreochromis niloticus) in ponds (Asian Journal of Medical and Biological Research, 2016)
Stocking density is considered one of the important factors affecting fish growth. The study was aimed to compare the growth parameters of monosex tilapia at various stocking densities. The experiment was carried out during the period from 06 August to 22 December 2014. Three stocking densities were used as 125, 250 and 375 fish/dec and designated as treatment T1, T2 and T3 respectively each having two replicates. All the fishes were of same age group having average initial body weight of 1.34g. A commercial feed was supplied at the rate of 40% of the body weight and then gradually it was readjusted to 20%, 10%, 5% and 3% respectively and continued up to the end of the experiment. The water quality parameters were monitored at 14 days interval and the ranges were: temperature 19.34 to 31.40°C, pH 6.83 to 8.03, dissolved oxygen 4.78 to 6.82 mg/l and transparency 29.02 to 49.45cm.The result of the present study showed that the mean weight gain was significantly (P